MANAJEMEN KURIKULUM KHAS DAARUT TAUHIID DI SMA DAARUT TAUHIID BOARDING SCHOOL PUTRA - Zakka, Muhammad Fikran Qinthara; Sururi, Sururi; Triatna, Cepi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the management of Daarut Tauhiid's distinctive curriculum at Daarut Tauhiid Boarding School Putra High School. The aim is to find out a clear picture of the management of the Daarut Tauhiid Specialized curriculum at Daarut Tauhiid Boarding School Putra High School. This research uses a descriptive method with a qualitative approach through interviews, documentation studies, and observations with the principal, vice principal for curriculum, teachers, and students as informants. The results of this study are that a structured and comprehensive approach in planning, organizing, implementing, and evaluating the curriculum has had a positive impact on the quality of graduates of SMA Daarut Tauhiid Boarding School Putra. This positive impact can be seen from the improvement in the quality of aqidah, worship, morals, memorization of the Qur'an, and academic achievement. Thus, the curriculum management of Daarut Tauhiid High School has succeeded in achieving its goals in shaping the character and academic achievement of students holistically.